Effects of neferine on retinal tissue in experimental diabetic rat model - Cevik, Mehmet; Gobeka, Hamidu Hamisi; Aydemir, Orhan (Springer, 2023)
Purpose To investigate vascular endothelial growth factor (VEGF) and proliferating cell nuclear antigen (PCNA) immunoreactivities, as well as apoptosis and oxidative stress levels in Streptozotocin (STZ)-induced diabetic rats, and determine how neferine affected these parameters. Methods Thirty-five male Sprague Dawley rats were divided into five groups of seven. Fasting blood glucose was measured 72 h after diabetes mellitus (DM) induction in 21 rats using 60 mg/kg STZ dissolved in 0.4 ml (0.1 M) sodium-citrate buffer (pH:4.5), with values > 250 mg/dl considered diabetic. Group 1 received no treatment. Group 3 (healthy rats) received daily intraperitoneal (IP) 4 mg/kg neferine. Following DM induction: Group 2 (sham) received daily IP 0.25 ml/kg 0.9% normal saline; Group 4 received single IP 0.01 mL (2.5 mg/kg) bevacizumab, followed by daily IP 0.25 mL/kg 0.9% normal saline; and Group 5 received daily IP 4 mg/kg neferine. Total antioxidant capacity (TAC) and total oxidative stress (TOS) levels in serum and ocular tissue homogenates were evaluated using ELISA. TUNEL method was used for determining apoptosis and immuno-histochemical staining for PCNA and VEGF immunoreactivities. Results Group 5 had significantly higher TAC and lower TOS in serum and ocular tissue homogenates than Group 4 (p < 0.05). Despite significantly lower VEGF levels and apoptosis (p < 0.05), there was no significant change in PCNA immunoreactivity in Group 5 (p > 0.05). Conclusions DM was associated with lower TAC, higher TOS and apoptotic cells, as well as VEGF and PCNA immunoreactivities in the retina. Neferine altered parameters other than PCNA in the opposite direction, demonstrating reductive effects on DM.
Keywords: Diabetic retinopathy; Neferine; Proliferating cell nuclear antigen; Rat; Total antioxidant capacity; Total oxidative stress